Evaluación del efecto de dos alternativas ecológicas en la mortalidad de insectos benéficos, abejas (Apis mellifera) y mariquitas (Coccinellidae) en el cultivo de Chocho (Lupinus mutabilis), cantón Salcedo provincia de Cotopaxi, 2021. - Alvarez Escobar, Tania Marisela (2021)
The research was carried out in Anchilivi sector, Canton Salcedo, Cotopaxi Province, at an altitude of 2728 meters above sea level, with the objective of evaluating the effect of two ecological alternatives on the mortality of beneficial insects: bees (Apis mellifera) and ladybugs (Coccinellidae), in the Lupinus crops (Lupinus mutabilis). A complete random designed was applied with a factorial arrangement of 2 x 2 x 2 + 2, giving a total of 16 treatments and 30 experimental units. The ecological alternatives were the lupine maceration with application doses of 100 gl-1 and 50 gl-1 and ozone with doses of 0.5 ppm and 0.3 ppm with one and two times of application, water and Cypermethrin 2 gl-1 were used as witnesses The percentage of mortality and the percentage of survival and external damages in each insect were the two variables to be evaluated. The capture of bees was done with an entomological net while the coccinellids were obtained from a hatchery, they were placed in entomological boxes of 0.40 m high and 0.40 m wide, covered with tulle cloth and inside of it a lupine plant in its flowering stage. The following results were obtained: the witness treatment T9 (water control) did not cause any damage to bees and ladybugs; in addition treatment T1 (Lupine macerate 100gl-1+1 application) reached to 4.47% of mortality in ladybugs; while for bees the treatments T3 (Lupine macerate 50gl-1+1application) and T7 (Ozone 0.3 ppm+1 application) had the lowest percentage of mortality, with an average of 4.44% and 4.45% respectively. In the lethal dose it was possible to determine that there was no statistical significance among the evaluated treatments in the ladybugs case, but there was in the bee’s case, where the two applications reached to a mortality percentage of 16.12%. (D1 High dose), for the Lupine macerate 100gl-1 and the Ozone to 0.5 ppm reached to 15.56% of mortality. The applied treatments caused external damages to the bees, all the treatments affected the eyes, also caused damages in the abdomen with T1 (Lupine macerate 100gl-1+1 application), T2 (Lupine macerate 100gl-1 + 2 applications), T4 (Lupine macerate 50gl-1 + 2 applications), T5 (Ozone 0, 5 ppm + 1 application) and T6 (Ozone 0,5 ppm + 2 applications); the corbicle was affected by the treatments with the Lupine macerate. The ladybugs had harmful effects in the eyes caused by all the treatments, the elytra were affected for all the treatments except by T7 (Ozone 0, 3 ppm + 1 application), the abdomen was only affected by T8 (Ozone 0,3 ppm + 2 applications) and there wasn’t any damage in the corbicle.